Ultra-fine characteristics of a sharpened image rendered by decreasing the critical low-intermediate frequencies as well as increasing the critical higher frequencies - Yang, Ching-Chung (Optik (Stuttgart), 2015)
We develop a modified high-pass filtering approach by using a 5×5 mask. The traditional filtering-mask here is separated to two respective ones weighed by different constants. One of them consists of four coefficients in the vertical and horizontal directions, relating to the critical higher frequencies. The other is with eight coefficients in different directions, relating to the critical low-intermediate frequencies. The merit of this masking was disclosed by employing nonlinear transfer functions, which had been proved liable to reduce the overshooting phenomenon. The final image is subject to acquire ultra-fine characteristics.